Experimental and Numerical Assessment of the Dynamic Behaviour of a Stress-Ribbon Bridge - Elsa Caetano (2004)
This paper describes the experimental and numerical study of the dynamic behaviour of a stress-ribbon footbridge constructed at the campus of the Faculty of Engineering of the University of Porto, Portugal. This bridge has not displayed any vibration problem, as yet, but significant levels of vertical oscillation have been observed under pedestrian use. Therefore, a site observation programme was developed in order to assess the main dynamic characteristics and levels of vibration of the bridge, to compare them with limit values recommended by structural codes, and to validate a numerical model to be used in predicting the bridge response under extreme loadings.